Oral corticosteroids (OCS), inhaled corticosteroids (ICS), short acting β-2 agonists (SABA), ICS/long acting β-2 agonists (LABA) treatment in pregnancy with asthma: a review - Septiyanti, Windy; Ramez Abdullah; Wahda Aqiedaty; Winda Kirana Ade Putri; Yuli Edy Saputra (Indonesian Journal of Pharmacology and Therapy, 2025)
Asthma is one of the common pulmonary disorders that can complicate pregnancy. Therefore, managing asthma is crucial for pregnant women's health and the well-being of the embryo. As consequence, it is important to evaluate the effectiveness and integrity of treatment for this usual therapy in expectant mothers with asthma. This review aimed to analyze the efficacy and safety of OCS, ICS, SABA, and ICS/LABA treatment in pregnancy with asthma. The articles were researched from PubMed, Scopus, and Science Direct as literature resources and selection of process based on inclusion criteria. The use of OCS, ICS, SABA, ICS/LABA were safe for pregnancy with asthma, although there are some side effects. In conclusion, the regiment therapy of asthma in asmathic pregnant women is similar to general treatment for asthmatic.